Toxemia gravídica: incidencia y morbimortalidad materna en el hospital II I pss Tarapoto 1989 -1993 - Orbe Flores, César Salomón (1994)
We performed a retrospective study from January 12, 1989 until December 31, 1993 in the Hospital II IPSS - Tarapoto, in order to determine the incidence and maternal morbidity and mortality from toxemia, 8699 medical records were reviewed was found only 122 cases , of which only 99 met the inclusion criteria, giving an incidence of 1.14% .. Of whom preeclampsia was presented by 78%. (21% mild preeclampsia and severe preeclampsia 57%) and 22% were eclampsia. The detected cases were in young mothers (14 to -25 years) and primigravid by 47%, they were not controlled or had poor prenatal care at 65.6%, were born by cesarean section 58% of cases of preeclampsia and 91% of cases of eclampsia, 52%. of deliveries completed in a gestational age ranging between 38-41 weeks. Postpartum morbidity was observed in 51% being the most frequent seizures, hypertension and infection (UTI and endometritis). 2 maternal deaths from eclampsia giving a mortality rate of 2..3 x 10000 nv found.